2007
DOI: 10.1002/hrdq.1190
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personality on training‐related aspects of motivation: Test of a longitudinal model

Abstract: A model that proposed dispositional influences on training-related aspects of motivation was developed. More specifically, the model predicted influences of the Big Five personality variables on motivation to learn and transfer motivation, while controlling for general attitudes toward training. The model was tested empirically, drawing on a sample of ninety-four employees from call centers who participated in a training program. Results indicated that motivation to learn was predicted by extraversion and agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 42 publications
7
88
2
7
Order By: Relevance
“…This is clear not only for the employers, but also for employees, who undertake various forms of vocational training (London & Smither, 1999a). Statistical data suggest that incomes of individuals involved in continuous education increase more rapidly than in those who do not show educational activity -this relationship was documented for both 2005and 2007(Czapiński & Panek, 2009.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…This is clear not only for the employers, but also for employees, who undertake various forms of vocational training (London & Smither, 1999a). Statistical data suggest that incomes of individuals involved in continuous education increase more rapidly than in those who do not show educational activity -this relationship was documented for both 2005and 2007(Czapiński & Panek, 2009.…”
Section: Introductionmentioning
confidence: 94%
“…Analysis of the available resources showed that many of the studies dealt with personality traits associated with the "Big Five" theory. Rowold (2007) found that extraversion alone could be associated with motivation to undertake training, whereas extraversion and agreeableness promote motivation for learning, and extraversion and emotional stability promote transfer motivation. Another study showed that motivation for learning is associated with proactive personality, openness to experience, extraversion and conscientiousness (Major et al, 2006).…”
Section: Personality Determinants Of Motivation To Undertake Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of CSE has been demonstrated in a variety of organizational constructs (e.g., Erez & Judge, 2001;Judge, 2009;Judge & Bono, 2001), and CSE's trait indicators have been repeatedly associated with learning and training (e.g., Stanhope, Pond, & Surface, 2013;Chen, Gully, & Eden, 2004;Rowold, 2007;Spector, 1982;Williams, Thayer, & Pond, 1991). In particular, Stanhope et al (2013) found that CSE related directly and indirectly to affective, cognitive, and skill-based learning.…”
Section: Core Self Evaluationmentioning
confidence: 99%